How Innovation affects Users’ Emotional Responses: Implications for Product Success and Business Sustainability. - Alonso-García, María; Moreno-Nieto, Daniel; Cabrera-Revuelta, Elena (MDPI, 2023)
The market is experiencing an expanding range of products, prompting manufacturing companies to differentiate themselves from competitors by moving away from conventional concepts. However, these innovations often fail to meet consumer expectations, leading to product failure, and consequently, an unsustainable evolution of the market and the business. This unsustainability requires designers to adapt innovations to align with consumer needs and desires. Understanding and validating these adaptations can be achieved by examining users’ emotional responses to innovative products. The objective of this study is to assess the influence of innovation in the development of new successful products, sales performance, and, therefore, business sustainability. This evaluation is based on the perceptions of potential consumers through the analysis of users’ emotional responses to various new product concepts at different design stages. A case study presents the evaluation of 48 new interactive lamp concepts categorized into relaxation, study, and leisure topics. The target audience for these concepts is consumers aged 18 to 24. The designs were developed by 12 teams of final-year industrial design students using insights from a prior psychographic study involving over 800 potential consumers. The findings highlight differences in users’ perceptions of innovative and traditional products across topics. These differences relate to users’ interest, intuitiveness, and desirability toward a product. Generally, traditional product concepts are perceived as more intuitive, but users show greater interest and desire for innovative concepts, with some variations among the analyzed topics. The business environment is encouraged to share these data with new product-development teams to achieve sustainable market and business growth.
Keywords: Desarrollo sostenible; Consumidores - Efectos de las innovaciones tecnológicas; Product evaluation; Innovation; Market sustainability; Design process; Business; Industrial design; Emotional response